Traditional risk factors and cancer-related factors associated with cardiovascular disease risk in head and neck cancer patients - Mukherjee, Amrita; Wiener, Howard W.; Griffin, Russell L.; Lenneman, Carrie; Chatterjee, Arka; Nabell, Lisle M.; Lewis, Cora E.; Shrestha, Sadeep (Frontiers in Cardiovascular Medicine, 2023)
Background: Risk of incident cardiovascular disease (CVD) in head neck squamous cell carcinoma (HNSCC) patients is under-reported. We assessed the association of HNSCC-related factors and traditional risk factors with one- and five-year CVD risk in HNSCC patients without prevalent CVD at cancer diagnosis. Methods: A clinical cohort of 1,829 HNSCC patients diagnosed between 2012 and 2018, at a National Cancer Institute (NCI)-designated cancer center was included. Information on HNSCC-related factors (HNSCC anatomical subsite, stage at diagnosis, treatment, and tumor human papillomavirus-HPV status) were extracted from the Tumor Registry. Data on traditional risk factors (hypertension, dyslipidemia, diabetes, tobacco smoking status, and obesity) were extracted from the electronic health records system (EHR) at baseline (HNSCC diagnosis). A composite of ischemic heart disease, heart failure, and ischemic stroke was the outcome of interest in time to event analysis. Hazard ratio (95%CI) were reported with death as a competing risk. Results: In patients diagnosed with HNSCC, 10.61% developed incident CVD events by one-year post cancer diagnosis. One-year CVD risk was lower in patients using antihypertensive medications at baseline, compared to patients without baseline hypertension [HR(95%CI): 0.41 (0.24-0.61). One-year CVD risk was high in patients receiving HNSCC surgery. Patients receiving radiation therapy had a higher five-year CVD risk than surgery patients [HR(95%CI): 2.17 (1.31-3.04)]. Patients using antihypertensive medications had a lower five-year CVD risk than patients without baseline hypertension [HR(95%CI): 0.45 (0.22-0.75)]. Older age and diabetes were associated with increased one- and five-year CVD risk. Human papillomavirus (HPV)-negative patients were older (p 0.006) and had a higher five-year cumulative incidence of CVD (p 0.013) than HPV-positive patients. Conclusion: Traditional risk factors and cancer-related factors are associated with CVD risk in HNSCC patients. Future research should investigate the role of antihypertensive medications in reducing CVD risk in HNSCC patients.